Pengaruh Media Microsoft Powerpoint Terhadap Hasil Belajar Pendidikan Agama Kristen Kelas VIII SMP Negeri 1 Sianjurmula-mula Kabupaten Samosir Tahun Pembelajaran 2023/2024 - Lidya Irmayani Manurung; Risden Anakampun; Taripar Aripin Samosir; Andar G. Pasaribu; Johari Manik (Jurnal Teologi Injili dan Pendidikan Agama, 2023)
The aim of this research is to find out that the learning outcomes of students taught with Microsoft Power Point media are higher than the learning outcomes of students taught without Microsoft Power Point Media for class VIII SMP Negeri 1 Sianjur for the 2023/2024 academic year. The research hypothesis is: "The learning outcomes of students in Christian Religious Education who are taught using Microsoft Power Point media are higher than the learning outcomes of students who are taught without Microsoft Power Point media in class VIII of SMP Negeri 1 Sianjur starting in the 2023/2024 academic year." This research method is a quantitative approach with a true experimental design method in the form of a Posttest-Only Control group design. The population is all Class VIII students of SMP Negeri 1 Sianjur Mulamula as many as 151 people and the sample was determined using a purposive sampling system, namely students in class VIII-4 totaling 30 people as an experimental class using Microsoft Power Point media and class VIII-5 totaling 30 people. as a control class that does not use Microsoft Power Point media. The instrument used in this research was a test with 33 questions. Research data for the test was analyzed using the Pool Variance t test formula. From the calculation results, the value of tcount = 4.941 > ttable(α=5%) = 1.671. The tcount value is in the curve area of ​​rejection of H0 and acceptance of Ha. Thus, it can be concluded that the research hypothesis is accepted, namely that there is an influence of Microsoft Power Point learning media on the learning outcomes of Christian Religious Education for class VIII students at SMP Negeri 1 Sianjur Mulamula for the 2023/2024 academic year. The difference in PAK learning outcomes in class VIII of SMP Negeri 1 Sianjur for the 2023/2024 academic year is known from the average Christian Religious Education learning outcomes for students using Microsoft Power Point media which is 0.80 higher than the average PAK learning outcomes for students. by not using Microsoft Power Point media, namely 0.71.